2012
DOI: 10.1007/s00264-012-1700-9
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage repair of the knee with Hyalograft C:® Magnetic Resonance Imaging assessment of the glycosaminoglycan content at midterm

Abstract: Purpose The aim of this study was to assess the stability of the glycosaminoglycan (GAG) content in the long term after matrix-associated autologous chondrocyte transplantation (MACT) with Hyalograft C in the knee over a follow-up period of one year. Methods In this cross-sectional evaluation, 11 patients after MACT of the knee consented to delayed gadoliniumenhanced magnetic resonance imaging of cartilage (dGEMRIC) measurements. The mean post-operative interval before the first MR examination was 40.6±22.0 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Autologous chondrocyte implantation is an established procedure for treatment of full cartilage defects in the knee joint with several satisfactory results in the literature [19][20][21][22][23]. Although little is known about cases when joint revision surgery is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous chondrocyte implantation is an established procedure for treatment of full cartilage defects in the knee joint with several satisfactory results in the literature [19][20][21][22][23]. Although little is known about cases when joint revision surgery is needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, Trattnig et al reported that T1-Gd was lower in repair tissue than in normal cartilage 2.8 and 4.7 years after MACI [23, 165]. About 4 and 5 years after MACI, a stable T1-Gd was observed by Brix et al [175]. T1-Gd was not significantly different between repair tissue and normal cartilage 9 to 18 years after ACI according to Vasiliadis et al [177].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies 3,6,15,22,23,26,30,33 found a statistical relationship between postoperative quantitative cartilage imaging values and PRO measures following cartilage repair and restoration, while 6 studies 2,7,12,20,25,29 found no statistical relationships between these parameters. The mean level of evidence (LoE) was not different between studies reporting a statistical relationship (LoE = 3.3 ± 0.9) and those that reported no statistical relationship (LoE = 3.0 ± 1.3; P = .67).…”
Section: Resultsmentioning
confidence: 99%